Borreliacidal activity of sera from hamsters infected with the Lyme disease spirochete. - Lovrich, S D (1991)
An in vitro borreliacidal assay that accurately reflects the levels of protective antibody determined by passive transfer of immunity studies was developed. Borreliacidal antibody in sera obtained from normal hamsters infected with Borrelia burgdorferi was readily detected. When immune serum containing complement was incubated with B. burgdorferi organisms, spirochetes were killed within 2 h. Treating immune serum with anti-hamster immunoglobulin G abrogated the borreliacidal activity. Killing of B. burgdorferi in serum was detected 1 week after infection; it peaked at week 3 and gradually declined. Relatively high levels of borreliacidal antibody were found, especially in week 3 immune serum, which could be diluted 1,280-fold. The decrease in borreliacidal antibody after infection may account for occurrences of reinfection and the remitting course of Lyme disease.